Development of thermosensitive hybrid hydrogels based on xylan-type hemicellulose from agave bagasse: characterization and antibacterial activity. (March 2020) - Arellano-Sandoval, L.; Delgado, E.; Camacho-Villegas, T.A.; Bravo-Madrigal, J.; Manríquez-González, R.; Lugo-Fabres, P.H.; Toriz, G.; García-Uriostegui, L.
Abstract: Abstract : This work focuses on the functionalization of agave xylan-type hemicellulose functionalized with trimethoxysilylpropylmethacrylate and crosslinked with N -vinylcaprolactam to obtain a thermoresponsive material for potential applications in drug delivery. The hydrogels showed an interconnected and porous architecture with a lower critical solution temperature (LCST) close to poly( N -vinylcaprolactam)'s (PNVCL) LCST. These materials showed a good capacity to load ciprofloxacin (in the range 9.5 × 10 −3 –8.4 × 10 −3 mg/mL), above the minimum inhibitory concentration (MIC ≤ 0.004 × 10 −3 –0.5 × 10 −3 mg/mL) for gram-positive and gram-negative bacteria. The hybrid hydrogel inhibited the growth of Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa .